2009
DOI: 10.1097/wnr.0b013e32832d0a67
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroimaging of mentalizing during the trust game in social anxiety disorder

Abstract: Individuals with generalized social anxiety disorder tend to make overly negative and distorted predictions about social events, which enhance perceptions of threat and contribute to excessive anxiety in social situations. Here, we coupled functional magnetic resonance imaging and a multiround economic exchange game ('trust game') to probe mentalizing, the social-cognitive ability to attribute mental states to others. Relative to interactions with a computer, those with human partners ('mentalizing') elicited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 25 publications
(37 reference statements)
7
64
0
Order By: Relevance
“…Recent work indicates that these biased cognitions may derive from an inability to infer how a social partner will view one’s social actions. To examine this possibility, Sripada and colleagues (71) used a trust game to compare neural responses when individuals were considering the actions of a real social partner or the actions of a computer partner. Individuals with social anxiety disorder showed diminished activity for social relative to nonsocial partners in a region of medial PFC implicated in theory-of-mind (72).…”
Section: Multiplayer Economic Games Quantify the Behavioral Dynamics mentioning
confidence: 99%
“…Recent work indicates that these biased cognitions may derive from an inability to infer how a social partner will view one’s social actions. To examine this possibility, Sripada and colleagues (71) used a trust game to compare neural responses when individuals were considering the actions of a real social partner or the actions of a computer partner. Individuals with social anxiety disorder showed diminished activity for social relative to nonsocial partners in a region of medial PFC implicated in theory-of-mind (72).…”
Section: Multiplayer Economic Games Quantify the Behavioral Dynamics mentioning
confidence: 99%
“…22,23 It is important to note, however, that while self-reported anxiety and sensitivity to negative stimuli are robustly observed, several studies reported no group differences in insula and amygdala reactivity. [24][25][26] This suggests that hyperactivation of emotion processing areas in patients with SAD depends on experimental details, such as stimulus type and modality 25 or task complexity. 26 In addition, increased activation during the processing of emotional faces has also been observed in other brain regions, such as the lateral and medial temporal and parietal cortices.…”
Section: Neural Correlates Of Aberrant Emotion Processing In Individumentioning
confidence: 99%
“…[24][25][26] This suggests that hyperactivation of emotion processing areas in patients with SAD depends on experimental details, such as stimulus type and modality 25 or task complexity. 26 In addition, increased activation during the processing of emotional faces has also been observed in other brain regions, such as the lateral and medial temporal and parietal cortices. 27,28 Few fMRI experiments have explicitly studied emotion regulation using pictorial stimuli in patients with SAD: Brühl and colleagues 29 instructed individuals with SAD to use the therapeutic emotion regulation strategy of "reality checking," during which the participant tries to evaluate the "complete reality" like an outside observer.…”
Section: Neural Correlates Of Aberrant Emotion Processing In Individumentioning
confidence: 99%
“…Sripada et al (2009) showed that patients with clinically significant social anxiety exhibited less activation of parts of this network during mentalizing compared with the results of matched healthy controls.…”
Section: Introductionmentioning
confidence: 99%